2021
DOI: 10.1186/s12864-021-07552-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome of the destructive oomycete Phytophthora cinnamomi provides insights into its pathogenicity and adaptive potential

Abstract: Background Phytophthora cinnamomi is an oomycete pathogen of global relevance. It is considered as one of the most invasive species, which has caused irreversible damage to natural ecosystems and horticultural crops. There is currently a lack of a high-quality reference genome for this species despite several attempts that have been made towards sequencing its genome. The lack of a good quality genome sequence has been a setback for various genetic and genomic research to be done on this specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 92 publications
3
54
0
Order By: Relevance
“…Several genomes of Phytophthora species contain hundreds of candidate RxLR effectors [20][21][22]29], and many of these effectors have been demonstrated by functional studies to contribute to virulence during host infection. In P. cinnamomi, recent studies have identified candidate RxLRs in the pathogen's genome [1,[23][24][25] but it remains unclear whether these putative effector genes are expressed during plant infection to contribute to virulence, and functions have yet to be assigned to any P. cinnamomi effectors. To that end, this study identified 61 candidate P. cinnamomi RxLR effector genes which are specifically expressed during the initial infection of avocado.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several genomes of Phytophthora species contain hundreds of candidate RxLR effectors [20][21][22]29], and many of these effectors have been demonstrated by functional studies to contribute to virulence during host infection. In P. cinnamomi, recent studies have identified candidate RxLRs in the pathogen's genome [1,[23][24][25] but it remains unclear whether these putative effector genes are expressed during plant infection to contribute to virulence, and functions have yet to be assigned to any P. cinnamomi effectors. To that end, this study identified 61 candidate P. cinnamomi RxLR effector genes which are specifically expressed during the initial infection of avocado.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a compilation of predicted candidate RxLRs in P. cinnamomi was created using data produced in previous studies [1,[23][24][25] as well as the set of 192 candidate RxLRs we identified in the P. cinnamomi genome using the pipeline developed by Win et al [22]. The final dataset consisted of 238 putative P. cinnamomi RxLRs with confirmed signal peptides.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations